(4d+3)(2d+7)=0

Simple and best practice solution for (4d+3)(2d+7)=0 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for (4d+3)(2d+7)=0 equation:


Simplifying
(4d + 3)(2d + 7) = 0

Reorder the terms:
(3 + 4d)(2d + 7) = 0

Reorder the terms:
(3 + 4d)(7 + 2d) = 0

Multiply (3 + 4d) * (7 + 2d)
(3(7 + 2d) + 4d * (7 + 2d)) = 0
((7 * 3 + 2d * 3) + 4d * (7 + 2d)) = 0
((21 + 6d) + 4d * (7 + 2d)) = 0
(21 + 6d + (7 * 4d + 2d * 4d)) = 0
(21 + 6d + (28d + 8d2)) = 0

Combine like terms: 6d + 28d = 34d
(21 + 34d + 8d2) = 0

Solving
21 + 34d + 8d2 = 0

Solving for variable 'd'.

Factor a trinomial.
(7 + 2d)(3 + 4d) = 0

Subproblem 1

Set the factor '(7 + 2d)' equal to zero and attempt to solve: Simplifying 7 + 2d = 0 Solving 7 + 2d = 0 Move all terms containing d to the left, all other terms to the right. Add '-7' to each side of the equation. 7 + -7 + 2d = 0 + -7 Combine like terms: 7 + -7 = 0 0 + 2d = 0 + -7 2d = 0 + -7 Combine like terms: 0 + -7 = -7 2d = -7 Divide each side by '2'. d = -3.5 Simplifying d = -3.5

Subproblem 2

Set the factor '(3 + 4d)' equal to zero and attempt to solve: Simplifying 3 + 4d = 0 Solving 3 + 4d = 0 Move all terms containing d to the left, all other terms to the right. Add '-3' to each side of the equation. 3 + -3 + 4d = 0 + -3 Combine like terms: 3 + -3 = 0 0 + 4d = 0 + -3 4d = 0 + -3 Combine like terms: 0 + -3 = -3 4d = -3 Divide each side by '4'. d = -0.75 Simplifying d = -0.75

Solution

d = {-3.5, -0.75}

See similar equations:

| 1=(x-54,166)/10,200 | | s=p/9 | | 4(2y+1)-(y-3)=2y+6 | | a-15=24 | | y=x^2-8+13 | | 2x+y=x-7 | | .4n-1/7=5 | | (cb)xa= | | -8+7+(-5)= | | (5/2)x+(1/4)x=(7/4)+x | | 1/2x=2x-6 | | 336=14v+2 | | 3[4-3x]-5[2x+3]=15 | | 2x+25=75+y | | 2sin^2x+5sing=3 | | 12+8x=180 | | 8+3n-3=9n+9-4n | | 3x/whenx=8andy=12 | | 3x+12-4=6 | | 14t=84 | | 8r(2r-5h)= | | 7s-14=-5+6s | | (4+5i)+x=(2-3i) | | (4+5i)+x=(2+3i) | | X=1/2(60-80) | | 2x-2+30=180 | | 7x+3x-6x-5=15 | | x-0.8=9.75 | | 8x-(5x-12)=39 | | -w^2+2w+5w^2-3= | | 8n-25=23+2n | | 2p(6p-9)= |

Equations solver categories